A Comparison of Beam Induced Damage from Xenon and Gallium Focused Ion Beams - Norris, Samuel (My University, 2019)
Focused ion beam/scanning electron microscopy (FIB/SEM) is a tool commonly used for applications including preparation of site-specific transmission electron microscopy (TEM) samples, nanotomography, and electronic circuit edit. Another potential application is optical device prototyping; however, the ion beam itself has been shown to cause damage fatal to device operation. This thesis first includes several examples of FIB-fabricated optical devices that had limited functionality compared to simulation. Second, the underlying causes of ion beam-induced optical damage from gallium and xenon ion sources is characterized. Monte Carlo simulations of ion-solid interactions were confirmed using TEM analysis to measure the thickness of the damaged layer. For crystalline samples such as silicon, Raman response can be used as a measure of lattice damage. Using these techniques, it was found that optical damage from a gallium beam is more severe than from a xenon beam, and occurs in the form of lattice amorphization and implantation of beam ions. This damage hinders optical coupling by altering the physical and electronic structure of the sample. Consequently, the xenon PFIB is a better choice for optical device prototyping.
Keywords: FIB; Ion beam; lithography; nanofabrication